Airway insertion first pass success and patient outcomes in adult out-of-hospital cardiac arrest: The Pragmatic Airway Resuscitation Trial. (January 2021) - Lesnick, Jason A.; Moore, Justin X.; Zhang, Yefei; Jarvis, Jeffrey; Nichol, Graham; Daya, Mohamud R.; Idris, Ahamed H.; Klug, Cameron; Dennis, David; Carlson, Jestin N.; Doshi, Pratik; Sopko, George; et al.
Abstract: Objective: While emphasized in clinical practice, the association between advanced airway insertion first-pass success (FPS) and patient outcomes is incompletely understood. We sought to determine the association of airway insertion FPS with adult out-of-hospital cardiac arrest (OHCA) outcomes in the Pragmatic Airway Resuscitation Trial (PART). Methods: We performed a secondary analysis of PART, a multicenter clinical trial comparing LT and ETI upon adult OHCA outcomes. We defined FPS as successful LT insertion or ETI on the first attempt as reported by EMS personnel. We examined the outcomes return of spontaneous circulation (ROSC), 72-h survival, hospital survival, and hospital survival with favorable neurologic status (Modified Rankin Scale ≤3). Using multivariable GEE (generalized estimating equations), we determined the association between FPS and OHCA outcomes, adjusting for age, sex, witnessed arrest, bystander CPR, initial rhythm, and initial airway type. Results: Of 3004 patients enrolled in the trial, 1423 received LT, 1227 received ETI, 354 received bag-valve-mask ventilation only. FPS was: LT 86.2% and ETI 46.7%. FPS was associated with increased ROSC (aOR 1.23; 95%CI: 1.07–1.41)), but not 72-h survival (1.22; 0.94–1.58), hospital survival (0.90; 0.68–1.19) or hospital survival with favorable neurologic status (0.66; 0.37–1.19). Conclusion: In adult OHCA, airway insertion FPS was associated with increased ROSC but not other OHCA outcomes. The influence of airway insertion FPS upon OHCA outcomes is unclear.